A Few Inequalities Established by Using Fractional Calculus and Their Applications to Certain Multivalently Analytic Functions - Irmak, Hüseyin (Chinese Journal of Mathematics, 2014)
By making use of different techniques given in Miller and Mocanu (2000) (and also in Jack (1971)), some recent results consisting of certain multivalently analytic functions given both in Irmak (2005) and in Irmak (2010) are firstly restated and some of their applications are then pointed out.